A novel c.290G>A mutation in the Factor 11 gene in a Dutch Caucasian family with a Factor XI deficiency. Issue 4 (April 2015) - Mulder, R.; Croles, F.N.; Lukens, M.V.; Meijer, K.; Mulder, A.B.
Highlights: We report a case of a 20-year old Dutch woman with a FXI activity level of 30 IU/dL. FXI deficiency occurs not only in Ashkenazi Jews, but also in Caucasians. We identified a novel c.290G>A mutation in the F11 gene. The c.290G>A mutation is associated with FXI deficiency.